Gottes Sprache in der philologischen Werkstatt : Hebraistik vom 15. bis zum 19. Jahrhundert - Veltri, Giuseppe; Necker, Gerold (Studies in European Judaism ;, 2004)
The present volume offers a fresh look at the crucial role which Christan Hebraism played in the development of the humanities and modern philology. Christian theology, Jewish tradition and linguistic interest had an irreversible impact on the understanding of holy texts and language.